2022
DOI: 10.3390/electronics11142276
|View full text |Cite
|
Sign up to set email alerts
|

Mindless Memorization Booster: A Method to Influence Memorization Power Using Attention Induction Phenomena Caused by Visual Interface Modulation and Its Application to Memorization Support for English Vocabulary Learning

Abstract: Memorization is necessary for various fields, such as language learning in the field of education. While memorization learning is often tedious and demotivating due to requiring conscious effort, few support approaches improve memorization unconsciously with low conscious effort. In this study, we propose a method, Mindless Memorization Booster, which improves users’ memorization unconsciously by visual stimuli of modulating the visual interface. This method is based on previous findings that the modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Another result also confirmed that AI could help students develop their critical thinking. It showed that students developed their critical thinking by discussing and predicting the visual generated by the AI (Futami et al, 2022). Shakirova (2007) agreed with this result, finding that the implementation of technology could positively impact critical thinking skills.…”
Section: Discussionsupporting
confidence: 58%
“…Another result also confirmed that AI could help students develop their critical thinking. It showed that students developed their critical thinking by discussing and predicting the visual generated by the AI (Futami et al, 2022). Shakirova (2007) agreed with this result, finding that the implementation of technology could positively impact critical thinking skills.…”
Section: Discussionsupporting
confidence: 58%
“…Duarte et al have revealed a psychological phenomenon like the placebo effect in which obtaining power-up items during a game actually changes the user's cognitive performance as well [29]. There is a method for lowering psychological stress during discussions by modifying the voices of oneself and others [9] and a visual interface to improve the recall speed of memorization learning [30].…”
Section: Related Workmentioning
confidence: 99%